Analisis Pemilihan Produk Bedak Padat Terbaik Berdasarkan Pilihan Konsumen Menggunakan Metode SMART - Leza Khairani; Zahra Nur Atthiyah; Agus Perdana Windarto (Explorer, 2023)
Facial beauty at this time can usually use cosmetics. Cosmetics have been known to people for centuries, and it was only in the 19th century that they received special attention as beauty. Cosmetics have become part of the business. Products used to enhance one's appearance are usually called cosmetics. Pressed powder is a type of cosmetic needed to complete facial makeup and is used to correct facial imperfections such as covering acne, dull skin, and facial blemishes. With so many counterfeit products out there, consumers are afraid to be careless in choosing pressed powder. So, in this article aimed at helping consumers decide which pressed powder is best for them, the authors used the SMART method to conduct research on pressed powder. In this article, data collection was carried out by distributing questionnaires to consumers via social media. In this article, 371 respondents were obtained using 5 criteria and 16 alternatives, and 132 respondents were randomly selected to be used as material to be processed using the SMART method. In this article, we have identified the best-pressed powder with the highest index value, namely the madam gie alternative with a value of 1. This research aims to assist consumers in choosing the best-pressed powder.